Neither cortical nor trabecular: An unusual type of bone in the heavy-load-bearing lower pharyngeal jaw of the black drum (Pogonias cromis). (1st March 2020) - Ziv, Efrat; Milgram, Joshua; Davis, Jonathan; Soares, Ana; Wilde, Fabian; Zaslansky, Paul; Shahar, Ron
Abstract: Durophagous fish consume a diet based primarily on hard-shelled animals, mainly mollusks. In order to successfully perform this task, they are equipped with an extra set of jaws located in their throat called pharyngeal jaws. Here we present the results of a study of the structure of the bony material of the exceptionally powerful lower pharyngeal jaws (LPJs) of the black drum Pogonias cromis which generate the highest biting forces documented in bony fishes. In particular, we studied the two long and slender struts that support the entire dental plate and teeth of the LPJ, in order to determine how this structure withstands the huge stresses it encounters repetitively and for long periods of time. We describe the hierarchical structure of the struts of lower pharyngeal jaw of P. cromis at a wide range of length scales, and show how it is adapted to successfully achieve its high mechanical performance. In particular, we show that the bone material of the strut is neither cortical nor cancellous, and although it is highly porous, its complex and layered three-dimensional arrangement of thick lamellae sheets, which are inter-connected by thin plates, is perfectly tailored to withstand extremely large but directionally-consistent forces. Statement of Significance: The diet of some fish consists of hard food, like mollusks and shells. In order to accomplish the task of cracking this type of food, they have an extra set of bony jaws located in their throat, called pharyngeal jaws. Here we describe the hierarchical structural elements of these jaws which allow them to withstand huge forces repeatedly over long periods of time. Surprisingly, the structure is very porous, but its architectural design is superbly adapted to handle consistently-oriented forces. This structural motif defines a new bony material which is neither cortical nor cancellous. Graphical abstract: Image, graphical abstract